Reforma psiquiátrica e atenção psicossocial: contextualização sócio histórica, desafios e perspectivas / Psychiatric Reform and psychossocial care in Brazil: sociohistorical contextualization, challenges and perspectives - Oliveira, Walter Ferreira de (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2013)
Este artigo faz um breve retrospecto da Reforma Psiquiátrica contextualizando social e historicamente a produção intelectual como meio para realização da atenção psicossocial, vista como um novo conjunto de dispositivos com fins de efetivar as propostas da Reforma. Analisa o impacto dos movimentos sociais das décdas de 1960 e 1970 no surgimento do Movimento de Reforma Psiquiátrica, até a promulgação da Lei 10.216/2001. Aponta, ao final, os desafios e os rumos da atenção psicossocial, considerando os rearranjos nas relações de poder e de hegemonia no campo da saúde mental. ABSTRACT: This article briefly reviews the the psychiatric reform in Brazil, contextuaizing the intellectual production as a means for the realization of psychossocial care. The latter is perceived as a field constituted by various elements for effecting the reformist proposals. The impact of the human rights movements of the 1960s and 70s is factored and the challenges and perspectives of the Reform are discussed, considering the rearrangements of power and hegemonical relationships within the mental health field. KEYWORDS: Psychiatric reform. Collective mental health. Psychossocialcare. Power. Hegemony.